2017
DOI: 10.1111/lcrp.12110
|View full text |Cite
|
Sign up to set email alerts
|

The effects of one versus two episodically oriented practice narratives on children's reports of a repeated event

Abstract: Purpose Previous research has found that children's reports of repeated events can be influenced by the presence and type of narrative practice in which they engage immediately prior to substantive recall. In particular, children's reports have been shown to benefit from practice providing narratives about an autobiographical repeated event. A gap remains, however, with regard to understanding whether practice narrating one episode of a repeated event encourages children to think about unique features of speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
(87 reference statements)
0
4
0
Order By: Relevance
“…All children in the current study received high quality episodic narrative practice, and many spontaneously provided labels for their practice events regardless of their Training condition. As such, the sparse effects of Training condition are unsurprising (see also Danby et al, ). Effects of Training condition were observed in spontaneity of labeling and accuracy scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All children in the current study received high quality episodic narrative practice, and many spontaneously provided labels for their practice events regardless of their Training condition. As such, the sparse effects of Training condition are unsurprising (see also Danby et al, ). Effects of Training condition were observed in spontaneity of labeling and accuracy scores.…”
Section: Discussionmentioning
confidence: 99%
“…Children aged 6 to 8 years participated in four sessions of a lab‐based repeated event and were interviewed 1 week later. All children practiced describing two specific instances of a repeated event from their own lives (Brubacher, Roberts, & Powell, ; Danby, Brubacher, Sharman, & Powell, ), but half of the children received explicit training in using deviations as labels for the instance being described (Label Training), whereas the other half of children did not receive this training (Standard Practice). Following the Practice phase, half of the children in each condition were asked to describe “what happens” across the series of target activities, followed by questioning about a specific instance (Generic‐first condition).…”
Section: Introductionmentioning
confidence: 99%
“…Children 5 to 9 years old ( N = 401, 54% female) were recruited from primary schools across Melbourne, Australia and surrounding areas to take part in several larger studies on children’s repeated event memory (Danby, Brubacher, Sharman & Powell, 2015; Danby, Brubacher, Sharman, Powell & Roberts, 2016; Danby, Brubacher, Sharman & Powell, 2017; Danby, Sharman, Brubacher, Powell & Roberts, 2017 ). Children were randomly assigned to the what ( n = 198, M age = 7.07, SD = 1.19) or why ( n = 203, M age = 7.08, SD = 1.23) conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence has shown that including NEP in the FI results in children and adolescents providing significantly more details in the substantive part of the interview than when NEP is omitted (Anderson et al, 2014). Brubacher et al (2011) have found that NEP is particularly important when interviewing children about repeated events and that having two episodically focused NEP opportunities has been found to increase the likelihood of obtaining episodic reports of repeated events compared to only one NEP opportunity (Danby et al, 2017). Because children and adolescents may experience multiple incidents of CSA (Roberts and Powell, 2001), including at least one, but preferably two, NEP opportunities in the rapport-building stage of an FI is important to maximize the likelihood of obtaining narrative reports of episodic rather than scripted memories of CSA in the substantive part of the interview.…”
Section: Importance Of Narrative Event Practicementioning
confidence: 99%